Jean Hellot. A pioneer of chemical technology - Jaime Wisniak (Revista CENIC Ciencias Químicas, 2009)
Jean Hellot (1685-1766) is considered one of the founders of the chemical, metallurgical, and textile industry in France and Europe. Although he published little, his impact was significant in the chemical revolution that took place in the nineteenth century. Hellot investigated zinc and its compounds, the precious metals, the preparation of phosphorus and ethyl ether, the manufacture of porcelain and invisible inks, and the mechanism of dyeing. An important discovery was the photo sensibility of paper impregnated with silver nitrate.